Identifikasi Nilai Ekonomi Ekosistem Hutan Mangrove Di Dusun Tanjung Tedung Kabupaten Bangka Tengah - Fitri Purnamasari; Wahyu Adi; Arief Febrianto (Universitas Bangka Belitung, 2022)
In the district of Tanjung Tedung there is mangrove ecosystem that grows along the coast of the district. The mangrove ecosystem in the Tanjung Tedung area is used by the community for fishing, shellfish cultivation and others, So that there is an economic value for the mangrove ecosystem in the district of Tanjung Tedung. This research was conducted from September 2018 to October 2019 in the Tanjung Tedung district, Tanjung Pura Village, Sungaiselan sun-district, Central Bangka Regency. As for the data that has been collected it consists of direct use value, indirect use value, option value, existence value and total economic value. Bases on the results of the identification of the economic benefist of the mangrove forest ecosystem the results for the direct use value of IDR 5.987.588.750,-/year, indirect use value IDR 3.780.569.250,-/year, option value IDR 376.532.100,-/year, exsistence value IDR 4.421.300.000,-/year, and fot the total economic value is IDR 14.565.990.100,-/year. The results of identification and economic valuation that have been carried out can provide an idea that the ecological and soci-economic benefits of mangrove ecosystem are quite large foe local communities.